Antimicrobial Effect of Hydroalcoholic Extract of Plantago Major Leaves with and without Zinc Oxide Nanoparticles on Streptococcus Mutans: An In Vitro Study - Sepide Safari; Reza Zare Mahmoodabadi; mohsen Arefnezhad; Shokouhsadat Hamedi; maryam mehrabkhani (Mashhad University of Medical Sciences, 2021)
Introduction: Resistance of oral pathogenic bacteria to chlorhexidine mouthwash is increasing; therefore, researchers are looking for a replacement of chlorhexidine with suitable herbal mouthwash. This study aimed to investigate the antimicrobial effect of hydroalcoholic extract of Plantago major (a native strain of Khorasan, Iran) with and without zinc oxide nanoparticles on Streptococcus mutans. Materials and Methods: In this in vitro study, the samples were tested in two groups of hydroalcoholic extract of Plantago major leaves with and without zinc oxide nanoparticles. To determine the minimum bactericidal concentration and minimal inhibitory concentration, agar diffusion and broth dilution methods were applied, respectively. A concentration of 500 ppm zinc oxide nanoparticles with a 0.4 nm diameter was used continuously in all stages of the experiment. The materials used in this study consisted of a standard strain of Streptococcus mutans (ATCC 25175), chlorhexidine 0.2% as a positive control, and distilled water as a negative control. Results: The mean diameter of the growth inhibition zone was obtained as 15±1 mm for the hydroalcoholic extract of Plantago major leaves with zinc oxide nanoparticles at a concentration of 1.56 mg/ml. The same extract at the same concentration, however without zinc oxide nanoparticles, showed the mean diameter of growth inhibition zone of 7.67±0.57 mm. The results of the t-test were indicative of a significant difference between the two groups (P-value<0.001). Conclusion: In this study, the antimicrobial effect of Plantago major leaves extract with or without zinc oxide nanoparticles was well established. This research is peculiar since it revealed the effectiveness of low concentrations of this plant in killing Streptococcus mutans.